2016
DOI: 10.1007/s11356-016-7093-3
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus adsorption on natural sediments with different pH incorporating surface morphology characterization

Abstract: Sediment samples from University Lake (U.L.) and Anacostia River (A.R.) were collected to study the phosphorus (P) adsorption with pH at 3.65, 4.75, and 5.65. The surface micro-morphology and pore structures of sediment particles were obtained using a scanning electron microscopy and gas adsorption method, respectively. Fourier analysis was then applied to approximate the surface morphology, which was incorporated into the Langmuir isotherm to directly derive the model parameters for P adsorption simulation. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…A near stable value is observed in the pH range 3-5 for S1 and 3-7 for S2, where dihydrogen phosphate (H 2 PO 4 -) is the prevalent species. This behavior has been observed in other studies of phosphate adsorption on sediments (Huang et al, 2016;Wang et al, 2005).…”
Section: Effect Of Solution Phsupporting
confidence: 84%
See 1 more Smart Citation
“…A near stable value is observed in the pH range 3-5 for S1 and 3-7 for S2, where dihydrogen phosphate (H 2 PO 4 -) is the prevalent species. This behavior has been observed in other studies of phosphate adsorption on sediments (Huang et al, 2016;Wang et al, 2005).…”
Section: Effect Of Solution Phsupporting
confidence: 84%
“…Despite several previous studies undertaken on phosphorus adsorption on sediments (Fang et al, 2013;Huang et al, 2015Huang et al, , 2016Zhou et al, 2005), no information about phosphorus sorption on sediments in mining zones characterized by high acidity is available in the literature. In addition, much research has been done on phosphate adsorption on iron oxyhydroxydes (Arai & Sparks, 2001;Boukemara et al, 2016;Elzinga & Sparks, 2007) but no study can be found in the literature about iron oxyhydroxy-sulfates which predominate in mining areas.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals exert significant negative impacts on the environment due to their abundance, persistence, and toxicity, which have been widely concerned by researchers [1][2][3]. Sediment particles, especially fine sediment particles, have a strong affinity to heavy metals in natural waters due to their specific surface area and surface active functional groups [4][5][6]. Thus, most heavy metal ions are average flow velocity decreased from 1.33 m/s in Chongqing to 0.22 m/s in Badong in 2015 [13].…”
Section: Introductionmentioning
confidence: 99%
“…The Standards, Measurements and Testing Program of the European Commission (SMT) method 20 defines a range of sediment P fractions that might be involved in release processes, including exchangeable labile P (ex-P), apatite P (Ca-P, calcium associated forms), non-apatite P (Fe/Al-P, the forms associated with oxides and hydroxides of Al, Fe, Mg and Mn), and organic P (OP); of these, ex-P, Fe/Al-P, and OP are considered as BAP and can easily release or be mineralized to water for maintaining its eutrophic state over a long term 6 . Other physicochemical components of the sediments, including the contents of fine particles 21 , organic matters (OM) 22 and hydratable metals, like Al and Fe 23 , all have negative relationship with sediment P release. On the other hand, P concentration in the water body can also directly influence the state of sediment P release.…”
mentioning
confidence: 99%
“…Therefore, when external P sources were controlled, P release from sediments would increase [25][26][27] . Other properties of the water column, such as pH 21,28 , oxygen status 29,30 , temperature 9,31 and flow conditions 32,33 , may all contribute to P release from sediments into the water column. To date, few studies have fully and systematically considered how these physicochemical factors of sediments and water column vary when small dams are constructed in river systems.…”
mentioning
confidence: 99%